Customer satisfaction towards life and family Takaful service (Etiqa as an operator) in Kepala Batas Pulau Pinang / Aziroh Osman - Osman, Aziroh (Faculty of Business and Management, 2011)
Insurance and Takaful are nowadays is not the wants of people anymore but it is ore to needs for life to be comfortable and more bright future. It is because this system will give protection to the persons under it. Regarding to this, customer are willing to make deal or business with the company that can offer the best profitable product and in excellent quality of service. Customer nowadays having more choice to choose the best for their complement and it is crucial for company to ensure their customers are satisfied with the service provided. Overall of this study will discuss the objective of is several objectives that researcher want to achieve. There are to determine the strength of service provided from Etiqa Takaful, to determine the level of customer satisfaction towards service quality provided by Etiqa Takaful and the last objective is to examine the relationship between factor contributing to customer satisfaction. Generally, customers are satisfied with the service provided, but this are not in the excellent stage of satisfaction. Company has to make some improvement to the quality of service so level of satisfaction can be increase. For the purpose of this study, researcher are using SPSS system in interpret the data collected. Frequency, descriptive and regression table are use to explain the result. Findings and analysis are interpreted in chapter four. Upon then, researcher is giving recommendation on the finding result to the company for some improvement in future.